Changing Patterns in Public Expenditure Management : An Overview - Premchand, A. (Washington, D.C. : International Monetary Fund, 1994)
Significant changes with far-reaching impact have taken place during recent years in public expenditure management. These changes which are being implemented in a few industrial countries are likely to be emulated by other industrial and developing countries. The content of these changes is enumerated in some detail, and their impact is assessed in terms of specified criteria. Other continuing problems that are not addressed by these advances are also considered in detail.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet